CURRENT STATE AND PERSPECTIVE OF DIAGNOSTICS OF NOSOCOMIAL PNEUMONIA IN THOSE INJURED WITH MULTIPLE TRAUMA - A. V. Prokhorov; Yu. Sh. Khalimov; S. V. Gayduk; S. V. Gavrilin; D. P. Meshakov; A. I. Chepel (Вестник анестезиологии и реаниматологии, 2018)
Trauma injuries account for high mortality and disability in the cohort of the employable population. Pulmonary infectious complications in those injured with multiple traumas contribute the most to mortality of such patients. The article describes risk factors, causative agents, pathologic physiology and specific features of diagnostics of nosocomial pneumonia in those with multiple traumas. Special attention is paid to study of state and variants of the immune response to multiple trauma and related issues on using polymorphism of genes controlling the release of certain cytokines in order to improve diagnostics and prognosis of the course and outcome of nosocomial pneumonia in this group of patients.